1985
DOI: 10.1007/bf00355566
|View full text |Cite
|
Sign up to set email alerts
|

Tantalum markers in radiography

Abstract: The biocompatibility of two types of radiopaque tantalum markers was evaluated histologically. Reactions to pin markers (99.9% purity) and spherical markers (95.2% purity) were investigated after 3-6 weeks in rabbits and 5-48 weeks in children with abnormal growth. Both marker types were firmly attached to bone trabeculae; this was most pronounced in rabbit bone, and no adverse macroscopic reactions were observed. Microscopically, no reactions or only slight fibrosis of bone tissue were detected, while soft ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Therefore, it is important to study the behavior of the cells on any nano-structure as a function of time before exploiting its use as an implant material. Tantalum metal has also been exploited as the material to engineer bone, dental implant [ 40 42 ] and also as a radiographic marker [ 43 ]. Moreover, once an implant geometry is experimentally verified to be apt for a particular application, various methodologies such as Nanoimprint lithography (NIL) as shown by Bergmair et al [ 44 ] or by indirect 3-Dimensional printing methods as demonstrated by Tamjid et al [ 45 ] can be employed to generate uniform nanotopographies of interest for improved bio-nanosurface interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to study the behavior of the cells on any nano-structure as a function of time before exploiting its use as an implant material. Tantalum metal has also been exploited as the material to engineer bone, dental implant [ 40 42 ] and also as a radiographic marker [ 43 ]. Moreover, once an implant geometry is experimentally verified to be apt for a particular application, various methodologies such as Nanoimprint lithography (NIL) as shown by Bergmair et al [ 44 ] or by indirect 3-Dimensional printing methods as demonstrated by Tamjid et al [ 45 ] can be employed to generate uniform nanotopographies of interest for improved bio-nanosurface interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, new materials such as TiO 2 , PDMS 47 48 , TCPS 49 are also consistently used to study the nature and modulation of interactions between cells and its micro/nano environment as a function of the size of surface features 50 . Owing to its excellent X-Ray visibility and magnetic susceptibility, Tantalum has also been widely exploited in fabricating stents 51 . Quite interestingly, cells not only respond differently to different sized nano surface features but also to the different shapes and roughness of the nanomaterial as is reported by Chen et al .…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to a delay in lymphatic drainage due to the previous surgery. Over the whole study term, all beads remained inert in the tissue as expected [39,40], with no migration out of the tendon tissue occurring. It is assumed that migration could potentially occur within the first six weeks after implantation [41].…”
Section: Clinical Examinationmentioning
confidence: 65%